STRATEGI TAKMIR DALAM MEMAKMURKAN MASJID AL-FURQAN - Isnaeni, Maryam Ulfa (Bayan lin-Naas : Jurnal Dakwah Islam, 2024)
The aim of this research is to find out how takmir's strategy is to make mosques prosperous through various da'wah activity programs. The method used is a qualitative method. Data collection was carried out to obtain data sources from research, namely by using interview, observation and documentation methods. The results of his research describe the takmir strategy of the Al Furqon mosque in its service to the community in the Nitikan Baru area, Sorosutan, Kec. Umbulharjo, Yogyakarta City, namely: carrying out sharing activities, carrying out routine studies, carrying out TPA activities, as well as savings program strategies. The role of the Al Furqon Mosque youth can drive the Al Furqon Mosque takmir's strategy in carrying out religious activity programs, because the existing youth are very active and directly involved in da'wah activities at the mosque.